2015
DOI: 10.1128/jvi.03246-14
|View full text |Cite
|
Sign up to set email alerts
|

A Viable Recombinant Rhabdovirus Lacking Its Glycoprotein Gene and Expressing Influenza Virus Hemagglutinin and Neuraminidase Is a Potent Influenza Vaccine

Abstract: The emergence of novel influenza viruses that cause devastating human disease is an ongoing threat and serves as an impetus for the continued development of novel approaches to influenza vaccines. Influenza vaccine development has traditionally focused on producing humoral and/or cell-mediated immunity, often against the viral surface glycoproteins hemagglutinin (HA) and neuraminidase (NA). Here, we describe a new vaccine candidate that utilizes a replication-defective vesicular stomatitis virus (VSV) vector b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…In contrast, the same intranasal inoculation with VSVΔG-CHIKV (n ϭ 8) and VLV (n ϭ 6) showed complete safety, with all mice surviving to the end of the experiment 42 days postinoculation. Although VSVΔG-H5N1 is nonpathogenic in adult mice outside the brain (45,46), here, we found it to be lethal after intranasal inoculation of P14 mice, with only a single survivor out of a large cohort (n ϭ 23) and almost all the mice succumbing to the virus within 4 to 10 days of inoculation (Fig. 4).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…In contrast, the same intranasal inoculation with VSVΔG-CHIKV (n ϭ 8) and VLV (n ϭ 6) showed complete safety, with all mice surviving to the end of the experiment 42 days postinoculation. Although VSVΔG-H5N1 is nonpathogenic in adult mice outside the brain (45,46), here, we found it to be lethal after intranasal inoculation of P14 mice, with only a single survivor out of a large cohort (n ϭ 23) and almost all the mice succumbing to the virus within 4 to 10 days of inoculation (Fig. 4).…”
Section: Resultsmentioning
confidence: 84%
“…All the chimeric viruses discussed here have shown efficacy in acting in a vaccine capacity to protect against the respective virus antigens, including Nipah virus, chikungunya virus, and influenza virus (44,(46)(47)(48)(49). By virtue of their safety in both adult and developing brains, VSVΔG-CHIKV and VLV showed the least adverse neurotropism among the chimeric viruses tested; these viruses merit further investigation for potential applications, including vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to create a vaccination strategy that exploits the advantages of live viral vectors, while at the same time limiting exposure to a single viral vector system, vesicular stomatitis virus (VSV) vectors with different vesiculovirus envelope proteins (17) have been generated that can be used in primeboost vaccination. We have previously shown that VSV vectors can express influenza HA molecules and that these VSV-HA constructs protect against challenge with homologous influenza viruses (18)(19)(20). Here, we show that VSV-cHA vaccines administered by different routes (intramuscular [i.m.]…”
mentioning
confidence: 90%